Theoretical Orientation of Mental Health Workers in Turkey - Savcı, Mustafa; Demır, Yasın; Kutlu, Mustafa; Aysan, Ferda (My University, 2018)
The aim of the study is to evaluate the primary theoretical orientation of mental health workers (psychiatrist, psychologist, psychological counselor and social worker) in Turkey. The study was conducted on 1073 (572 women, 501 men) mental health workers, including 133 psychiatrists, 312 psychologists, 430 psychological counselors, and 198 social workers. Mental health workers between the ages of 22 and 73, from every city in Turkey participated in the study. Personal Information Form designed by the researchers was used as data collection tool in the study. Personal Information Form was emailed to the professionals and the data was collected online. Collected data were analyzed by frequency and percentage calculations. The findings of the study demonstrated that the primary theoretical orientation of psychiatrists and psychologists were cognitive behaviorist therapy, of psychological counselors were constructivist therapy and of social workers were system/family systems therapies. Furthermore, it was observed that the least preferred psychotherapy approach by the professionals was the multi-cultural therapy. The results of the study were discussed within the realm of the literature, and recommendations were presented for mental health workers and researchers.
Keywords: Psikoloji